Conceptualizing Technical and Vocational Education and Training as a Service Through Service-Dominant Logic - Jinfang Cai; Michitaka Kosaka (SAGE Open, 2024)
Technical and vocational education and training (TVET) plays a pivotal role in equipping young individuals with technical skills and competencies, enhancing their employability. TVET is distinct for its student-centered and industry-oriented features, often involving enterprises in on-site training. In this study, we conceptualized TVET as a service through the lens of service-dominant (S-D) logic, offering a comprehensive exploration of its attributes and values. Our work rigorously validates the fundamental premises of S-D logic within the context of TVET, making the first systematic examination of TVET from a service science perspective. This innovative conceptualization allows us to view TVET as a dynamic process of value co-creation, with students and enterprises as active co-creators. They collaborate and contribute, fostering profound engagement among TVET practitioners, to mitigate TVET challenges through co-creation.